Extensive lysine acetylation occurs in evolutionarily conserved metabolic pathways and parasite‐specific functions during Plasmodium falciparum intraerythrocytic development. Issue 4 (12th July 2013) - Miao, Jun; Lawrence, Matthew; Jeffers, Victoria; Zhao, Fangqing; Parker, Daniel; Ge, Ying; Sullivan, William J.; Cui, Liwang
Summary Lysine acetylation has emerged as a major post‐translational modification involved in diverse cellular functions. Using a combination of immunoisolation and liquid chromatography coupled to accurate mass spectrometry, we determined the first acetylome of the human malaria parasite Plasmodium falciparum during its active proliferation in erythrocytes with 421 acetylation sites identified in 230 proteins. Lysine‐acetylated proteins are distributed in the nucleus, cytoplasm, mitochondrion and apicoplast. Whereas occurrence of lysine acetylation in a similarly wide range of cellular functions suggests conservation of lysine acetylation through evolution, the Plasmodium acetylome also revealed significant divergence from those of other eukaryotes and even the closely related parasite Toxoplasma. This divergence is reflected in the acetylation of a large number of Plasmodium‐specific proteins and different acetylation sites in evolutionarily conserved acetylated proteins. A prominent example is the abundant acetylation of proteins in the glycolysis pathway but relatively deficient acetylation of enzymes in the citrate cycle. Using specific transgenic lines and inhibitors, we determined that the acetyltransferase PfMYST and lysine deacetylases play important roles in regulating the dynamics of cytoplasmic protein acetylation. The Plasmodium acetylome provides an exciting start point for further exploration of functions of acetylation in the biology of malaria parasites.